The correlation between self-related adherence, asthma-related quality of life and control of asthma in adult patients - Elida Zairina, - (Walter de Gruyter, 2021)
Objectives: Medication non-adherence mostly occurs in patients with a wide range of disease severity, including asthma. The aim of the study was to assess the self reported adherence to asthma therapy and investigate the relationship between adherence, asthma control and asthma-related quality of life.